2021
DOI: 10.1108/jaoc-04-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Risk-based management control resistance in a context of institutional complexity: evidence from an emerging economy

Abstract: Purpose The purpose of this study is to examine the impact of competing logics on the implementation of risk-based management controls (RBMC) by providing evidence of resistance due to competing logics. Moreover, the study proposes solutions to logic contestation. These solutions may help the company override logic complexity. Design/methodology/approach This study draws upon the theory of institutional logics. It adopts an interpretative qualitative research approach and uses the case study method. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…The COVID-19 pandemic contributed to more pressures from international rating agencies and international reinsurers upon insurers to embed enterprise risk management (ERM), which necessitates the adoption of Solvency II capital adequacy requirements (Metwally and Diab, 2021). Within the present context, where several risks have emerged following the COVID-19 pandemic, it is expected that the risk management (RM) department would play a key role in setting the company strategy and promoting its financial and operational resilience (Naseeb et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic contributed to more pressures from international rating agencies and international reinsurers upon insurers to embed enterprise risk management (ERM), which necessitates the adoption of Solvency II capital adequacy requirements (Metwally and Diab, 2021). Within the present context, where several risks have emerged following the COVID-19 pandemic, it is expected that the risk management (RM) department would play a key role in setting the company strategy and promoting its financial and operational resilience (Naseeb et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The rise of ERM has inspired more studies to examine its conceptualisation and interactions with organisational apparatuses and how that led to new modes of controls (Bhimani, 2009; Huber and Scheytt, 2013; Tekathen and Dechow, 2013; Vinnari and Skaebaek, 2014). However, most of these studies focus on the risk-based management practices in both the west and least-developed countries (LDCs) (Metwally and Diab, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He further argues that already institutionalized structures and procedures can legitimize the adoption of new structures or procedures. When existing institutionalized elements are used to legitimate new elements, the new elements tend to be more acceptable and effective (Zucker, 1987); otherwise, the implementation of a new system such as ERM will likely face resistance from people in the companies (Metwally and Diab, 2021). Soin and Collier (2013) argue that ERM has become the central theme of management control systems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Based on an experimental study using 92 certified external auditors, they find that external auditors' reliance on the ERM advice from the internal auditors is highest when the internal auditors are under the supervision of a strong audit committee. Metwally and Diab (2021) use an interpretative qualitative research method to obtain data from insurance companies in Egypt through interviews, observations and a review of documents. They found that the ERM implementation produces heterogenic practices that change the companies' existing control system leading to resistance from employees because the institutionalization of ERM challenges the traditional work environment and organizational culture.…”
Section: Introductionmentioning
confidence: 99%